Development of Project-Based Electronics Practicum Module with Virtual Lab to Increase Students’ Creativity - Putu Widiarini; Ni Ketut Rapi; I Putu Wina Yasa Pramadi; Ketut Wira Udayana (Jurnal Penelitian Pendidikan IPA, 2022)
One alternative source of learning physics can be a project-based practicum module with a virtual laboratory, especially for increasing student creativity. The purpose of this research is to develop a valid, practical, and effective project-based electronics practicum module with a virtual lab. The validity of the module is obtained from the validation results by three validators, namely content experts, learning experts, and media experts. The practicality of the module is obtained by giving response questionnaires to one lecturer in an electronics course and 12 students in semester 5A of the Physics Education study program. The effectiveness of the module is obtained by giving a project that can increase students’ creativity. The developed module is very valid with an average validity of 3.70. The developed module is very practical with average practicality of 3.76. The effectiveness of the module is in the moderate category with a normalized average gain score of 0.51. The results show that the developed module is very valid, very practical, and effective so that it can be used as one of the teaching materials in electronics lectures